1995
DOI: 10.11150/kansenshogakuzasshi1970.69.1356
|View full text |Cite
|
Sign up to set email alerts
|

Legionella pneumophila Serogroup 3 Isolated from a Patient of Pneumonia Developed after Drowning in Bathtub of a Hot Spring Spa

Abstract: A 71-year-old Japanese female, was found unconscious by drawing, in a hot spring spa, at around noon of 20 October 1994. She recovered by emergency cardiopulmonary resuscitation, and admitted to the Takinomiya General Hospital, with adult respiratory distress syndrome (ARDS). Although she recovered from ARDS within 4 days after her admission, she developed severe pneumonia accompanied with the second attack of ARDS. Ordinary bacteriological culture of her respiratory specimens failed to yield any significant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 4 publications
1
13
0
Order By: Relevance
“…This is the second case report of Legionella pneumonia due to Legionella pneumophila serogroup 3 in Japan. Shiota et al first reported a case in 1995 and successfully treated that patient with minocycline and erythromycin (33). In the present case, the laboratory detection of Legionella pneumonia was clear after the patient died.…”
Section: Discussionsupporting
confidence: 47%
“…This is the second case report of Legionella pneumonia due to Legionella pneumophila serogroup 3 in Japan. Shiota et al first reported a case in 1995 and successfully treated that patient with minocycline and erythromycin (33). In the present case, the laboratory detection of Legionella pneumonia was clear after the patient died.…”
Section: Discussionsupporting
confidence: 47%
“…In Japan, incidences of Legionnaires' disease with the causative agents probably originating in spas have been described (14,15) and there is a reported outbreak involving 3 patients in Iwate Prefecture in 1999 (16). Thus we concluded that the present outbreak was the largest mass epidemicof legionellosis, involving a bathhouse as a source of infection, in which heated water was continuously circulated.…”
Section: Discussionmentioning
confidence: 99%
“…Yabuuchi et al (16) reported that legionellae inhabited the bath water of 84 (62.2%) of the 135 Japanese hot springs investigated. At a therapeutic thermal spa in Portugal, Rocha et al (10) showed an association between exposure to hot spring water and an increase in antibody titers against the majority of species Recently, we isolated L. pneumophila serogroup (SG) 3 from a patient who developed pneumonia after nearly drowning in a hot spring spa bath (12), but the infection source remained to be determined because the viable number of legionellae (3 CFU/100 ml) in the probable source of the infection were of low risk for causing legionellosis. We describe the molecular determination of the infection source of this sporadic Legionella pneumonia case associated with the hot spring bath, and also discuss the usefulness of PCR fingerprinting in epidemiological investigations.…”
mentioning
confidence: 99%